The (Self-)Funding of Intangibles - Robin Döttling; Tomislav Ladika; Enrico Perotti (Tinbergen Institute, 2016)
In response to technological change, U.S. corporations have been investing more in intangible capital. This transformation is empirically associated with lower leverage and greater cash holdings, and commonly explained as a precautionary response to reduced debt capacity. We model how firms' payout and cash holding policies are affected by this shift. Our insight is that the creation of intangibles is largely achieved by human capital investment and requires lower upfront outlays. Firms can self-finance the retention of human capital by granting deferred equity compensation. Interestingly, retaining cash and repurchasing shares enhances the value of unvested equity, thereby facilitating retention and reducing equity dilution. Our empirical evidence confirms that firms with higher intangible investment have lower upfront investment needs. They make similar payouts as tangible investment firms, suggesting they are not on average more financially constrained. They also tend to grant more deferred equity and prioritize repurchases over dividends in particular when their stock volatility is high, in line with our model's predictions.
Keywords: G32; G35; J24; J33; 330; Technological change; corporate leverage; cash holdings; human capital; intangible capital; equity grants; deferred equity; share vesting